Lakshmi and Me - Jain, Nishtha (Nevatia, Smriti, 2007)
Verzio FF submission Duration: 00:59:00 This personal film turns the camera on the director's maid Lakshmi. She works nearly 10 hours a day, seven days a week for a number of Mumbai families, earning in a month what her employers would spend on a good meal. Dress, family relations anchored in tradition, her relations to education, doctors, male and female family roles – in almost everything Lakshmi is different from the families who can afford to employ her. The director eloquently illustrates this point in a number of scenes, such as when the protagonist chooses to eat sitting on the ground at her employer's luxury flat. As well as its Indian elements, the film focuses on questions linked to the justice of work and equality between different social classes. Lakshmi works though she is pregnant, weighs only 44 kilograms and has to deal with serious health problems. The director gradually turns away from the flats of Lakshmi's employers and turns the camera on the subject's own living conditions.